URGENCY OF MANAGERIAL SKILLS FOR GUIDANCE AND COUNSELING TEACHERS IN SCHOOLS - Kanaya Yose Putri; Neviyarni Neviyarni; Yarmis Syukur; Ahmad Wahid (Jurnal Manajemen Pendidikan, 2026)
The central role of management in guidance and counseling requires counseling teachers to be able to implement these management functions optimally. Doing management is not as easy as imagined, requiring a lot of drive and skills, including one of which is managerial skills. This study was conducted with the aim of conducting a critical and thorough study of how the urgency of managerial skills for guidance and counseling teachers in carrying out management of all their activities. The method applied in this research is literature review. The conclusion from this study is that managerial skills are of high urgency to improve the effectiveness of guidance and counseling management implementation. This skill is a key aspect in an effort to create quality and useful management. An in-depth review of credible literature has also revealed that strong managerial skills can enhance organizational performance, productivity, and achievements, particularly in school guidance and counseling organizations. Therefore, this study recommends that guidance and counseling teachers and related stakeholders begin developing and improving the managerial skills of school counselors. Many efforts can be made, such as participating in training activities, workshops, seminars and so on.